You have to multiply whats outside the parenthesis with everything that is inside, so
![x^{-3}y^0.(x^2-3x^5y^4)](https://tex.z-dn.net/?f=x%5E%7B-3%7Dy%5E0.%28x%5E2-3x%5E5y%5E4%29)
![x^{-3}y^0.x^2-x^{-3}y^0.3x^5y^4](https://tex.z-dn.net/?f=x%5E%7B-3%7Dy%5E0.x%5E2-x%5E%7B-3%7Dy%5E0.3x%5E5y%5E4)
Multiplication of same bases we sum the exponents
![x^{-3+2}y^0-3x^{-3+5}y^{0+4}](https://tex.z-dn.net/?f=x%5E%7B-3%2B2%7Dy%5E0-3x%5E%7B-3%2B5%7Dy%5E%7B0%2B4%7D)
![x^{-1}.1-3x^2y^4](https://tex.z-dn.net/?f=x%5E%7B-1%7D.1-3x%5E2y%5E4)
![x^{-1}-3x^2y^4](https://tex.z-dn.net/?f=x%5E%7B-1%7D-3x%5E2y%5E4)
Alternative B.
Evaluating each expression means to simplify the expression down to it's simplest form.
Answer:
Answer:
y=
d−4
/c+9
Step-by-step explanation:
cy+4=d−9y
Step 1: Add 9y to both sides.
cy+4+9y=d−9y+9y
cy+9y+4=d
Step 2: Add -4 to both sides.
cy+9y+4+−4=d+−4
cy+9y=d−4
Step 3: Factor out variable y.
y(c+9)=d−4
Step 4: Divide both sides by c+9.
y(c+9) c+9
=
d−4
/c+9
y=
d−4
/c+9
Answer:
1014cm^2
Step-by-step explanation:
find the area of one side and times it by 6 (bc a cube has 6 sides)
13×13=169
169×6=1014
Equation in <span>slope intercept form
y = -7x + 6
hope it helps</span>